Memahami Objektivitas Dalam Penilaian Moral - Fakhruddin Fakhruddin (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2017)
Can moral judgment be objective'' Unlike scientific judgment, moral judgment is often considered simply subjective. This article is an attempt to argue against this contention. The article is divided into three parts, First, as a background for the problem, it will be shown how the scientistic view of reality and its limited view of objectivity has given rise to the problem of objectivity in moral judgment. Second, to see the similarities and differences between the concept of objectivity in scientific judgment and in moral judgment, the two will be compared. Third, to bolster the argument for supporting the idea of objectivity in moral judgment, some criteria for the objectivity of moral judgment will be provided.